Tinjauan Yuridis Kekerasan dalam Rumah Tangga oleh Suami (Putusan NO.135/PID.SUS/2021/PN MTW) - Bahrul Soleh Pujia Nusantara; Ermania Widjajanti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the legal considerations of judges in rendering decisions against perpetrators of domestic violence committed by husbands as reflected in Decision Number 135/Pid.Sus/2021/PN Mtw, and to examine the application of Law Number 23 of 2004 concerning the Elimination of Domestic Violence in the decision. This research employs a normative juridical method using statutory and case approaches. Data were obtained through library research consisting of primary, secondary, and tertiary legal materials relevant to the research issue. The analysis was conducted qualitatively by examining judicial reasoning based on trial facts, valid evidence, and applicable legal provisions. The findings indicate that the judge comprehensively considered the elements of the criminal act of physical violence as stipulated in Article 44 paragraph (1) of Law Number 23 of 2004. The decision also reflected juridical, sociological, and philosophical considerations in determining the defendant’s guilt. The imposed criminal sanction was deemed proportional as it balanced aggravating and mitigating circumstances appropriately. The implementation of the law in this case demonstrates consistency in law enforcement and a commitment to protecting victims of domestic violence. Nevertheless, greater public legal awareness and the optimization of law enforcement roles remain necessary to prevent similar acts of violence in the future.